(untitled) (Revista de História da UEG (REVHIST), 2023)
The liberalization of law in the Empire of Brazil was adversely affected by the continuity of the slave regime, giving rise to the liberalism-slavery dichotomy. In the light of this, we examine the "criminal policy" and the economy of this time, through a key of biopolitical analysis. Thus, we are faced with a mechanism of power that updated techniques of extermination from the colonial period, in a very different legal environment, serving as a kind of apocryphal legitimation for the direct and indirect murder of black people, especially the enslaved ones. This political-economic strategy can be called “black delinquency.” This paper aims to scrutinize its invention, in other words, the construction of black people as a public enemy. Keywords: Black delinquency. Empire of Brazil. Law. Slave economy.